-20n+6(16+16n)=-12(n-8)

Simple and best practice solution for -20n+6(16+16n)=-12(n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20n+6(16+16n)=-12(n-8) equation:


Simplifying
-20n + 6(16 + 16n) = -12(n + -8)
-20n + (16 * 6 + 16n * 6) = -12(n + -8)
-20n + (96 + 96n) = -12(n + -8)

Reorder the terms:
96 + -20n + 96n = -12(n + -8)

Combine like terms: -20n + 96n = 76n
96 + 76n = -12(n + -8)

Reorder the terms:
96 + 76n = -12(-8 + n)
96 + 76n = (-8 * -12 + n * -12)
96 + 76n = (96 + -12n)

Add '-96' to each side of the equation.
96 + -96 + 76n = 96 + -96 + -12n

Combine like terms: 96 + -96 = 0
0 + 76n = 96 + -96 + -12n
76n = 96 + -96 + -12n

Combine like terms: 96 + -96 = 0
76n = 0 + -12n
76n = -12n

Solving
76n = -12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12n' to each side of the equation.
76n + 12n = -12n + 12n

Combine like terms: 76n + 12n = 88n
88n = -12n + 12n

Combine like terms: -12n + 12n = 0
88n = 0

Divide each side by '88'.
n = 0

Simplifying
n = 0

See similar equations:

| 3y^2=-7-4 | | -21y=-765 | | 3n+18=-24 | | 2x^7/2x^3/13 | | 1/3(9x+5)=5(x-1)-6 | | 4b^2+(-7)b=0 | | 2a+6=a-8 | | f(x)=2x^2-5x-3 | | -3h+4.2=55-11h | | 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 | | 8x^2-22x-90=0 | | 7mx^2+2nx^2-7my^2-2ny^2=0 | | 7/5-3/8(136/15)=-2 | | 25+4(-4x+5)= | | 14z=0 | | 8/3x^2-5/4x | | 1/2x=11/14+4/7 | | 7/5-3/8(136/15) | | 17-(6x+3)-2x+4= | | ((3(x-4)/4)/4)=4x-4 | | 6a^2+27a-15=0 | | 7x+2y=26 | | 75/3*25= | | 10w-14wv-15w+21v=0 | | 3(x-8)=4(x+2) | | -2[6x+1]=4[x-5]-2 | | -12*(6-4)+2= |

Equations solver categories